Proximate Analysis of Rice Husk Waste Briquettes and Dried Leaves as Alternative Fuel - Syaiful Mansyur; Andri Prasetyo Nugroho (Universitas Proklamasi 45, 2025)
One of the uses of rice husk waste is to make it into fuel, not only to replace firewood as fuel for cooking in the household but also to grill various types of food tailored to its application. Then, to optimize rice husk into fuel, it needs to be compacted or densified into charcoal briquettes, because with a good densification process, the calorific value of rice husk can be higher than before it is compacted. Densification of biomass or other solid fuels can increase the energy density, making it more efficient as an energy source. In this study, an experimental analysis process was carried out to optimize the briquette-making process so that it could improve combustion efficiency and quality according to Indonesia standards. The results showed that the addition of dry leaf charcoal to make briquettes of a mixture of rice husks and leaves significantly, with a value of F = 0.0346, can increase the calorific value of briquettes according to Indonesian Standards. For proximate test values of water content and volatile content, significant values of 0.039 and 0.012 were obtained, respectively, so these results show the effect of adding dry leaves and reducing the percentage of husk charcoal significantly. While other test results, namely the value of ash content and bound carbon, did not have a significant effect both when adding leaf charcoal and reducing husk charcoal with a significance value of 0.21 and 0.054, respectively, this is because husk charcoal has silica, which can increase ash content, and the physical structure of the two materials is less dense.